2017
DOI: 10.1292/jvms.16-0484
|View full text |Cite
|
Sign up to set email alerts
|

First molecular detection of tick-borne pathogens in dogs from Jiangxi, China

Abstract: In this study, blood samples obtained from 162 dogs in Jiangxi, China, were employed in molecular screening of canine tick-borne pathogens by PCR and sequencing. Babesia spp. gene fragment was detected in 12 (7.41%) dogs. All samples were negative for Hepatozoon spp., Ehrlichia canis, Coxiella spp., Borrelia spp., Rickettsia spp. and Anaplasma platys. Species-specific PCR analysis further confirmed that 8 (4.94%) and 4 (2.47%) dogs were infected by Babesia canis vogeli and Babesia gibsoni, respectively. Based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 31 publications
2
24
0
Order By: Relevance
“…B. gibsoni is the most widespread species in China; it has been reported in Shandong, Jiangsu, Anhui, Shanghai, Zhejinag, Nanjing, Jiangxi, and Guangxi. B. canis vogeli is the other species reported in dogs, whose epidemic areas include Jiangxi and Gansu (Wei et al, 2012 ; Yao et al, 2014 ; Niu et al, 2017 ; Zheng et al, 2017 ). Very recently, Niu et al reported T. sinensis in pet dogs in Gansu, representing the first report of T. sinensis in dogs (Niu et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…B. gibsoni is the most widespread species in China; it has been reported in Shandong, Jiangsu, Anhui, Shanghai, Zhejinag, Nanjing, Jiangxi, and Guangxi. B. canis vogeli is the other species reported in dogs, whose epidemic areas include Jiangxi and Gansu (Wei et al, 2012 ; Yao et al, 2014 ; Niu et al, 2017 ; Zheng et al, 2017 ). Very recently, Niu et al reported T. sinensis in pet dogs in Gansu, representing the first report of T. sinensis in dogs (Niu et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Yao et al reported that B. gibsoni is the main species responsible for canine babesiosis in Nanjing (Yao et al, 2014 ). In Jiangxi, the rates of positivity for B. canis vogeli and B. gibsoni are 4.94 and 2.47%, respectively, as tested by species-specific PCR (Zheng et al, 2017 ). In 2017, Niu et al first reported the identification of Theileria sinensis in pet dogs from Gansu province of China, providing the first report of T. sinensis in dogs worldwide (Niu et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…infections in dogs continue to increase worldwide, primarily in many developing countries but also in several developed countries. Previous epidemiological studies regarding Babesia infection in dogs and ticks demonstrated that four species of Babesia were circulating in China, and B. gibsoni was the predominant pathogen causing babesiosis in the central, southern and eastern regions of China [ 18 – 20 , 22 , 23 , 38 ]. However, little information concerning the epidemiology of Babesia spp.…”
Section: Discussionmentioning
confidence: 99%
“…As the most prevalent Babesia species, B. gibsoni is responsible for canine babesiosis in the central, southern and eastern regions of China, as well as Taiwan [15][16][17][18][19][20]. Babesia vogeli has been identified in dogs in Gansu, Jiangxi, Guangdong and Hunan provinces [21,22] and in ticks in Henan [23]. Babesia canis has been reported in dogs in Henan [24] and various 18S rRNA gene sequences of B. canis have been identified in dogs and ticks in Hunan and Qinghai provinces, respectively.…”
mentioning
confidence: 99%
“…To date, at least three protozoan ( Theileria, Babesia and Hepatozoon ) and five bacterial ( Anaplasma, Ehrlichia, Rickettsia, Coxiella and Bartonella ) tick-borne genera have been reported in domestic dogs around the globe (Beck et al 2009 ; Brown et al 2006 ; Buhariwalla et al 1996 ; Camacho et al 2001 ; Conrad et al 1991 ; Kaewkong et al 2014 ; Kamani et al 2013 ; Levin et al 2012 ; Mokhtar et al 2013 ; Yabsley et al 2008 ). In Jiangxi Province, mid-eastern China, Babesia canis vogeli and Babesia gibsoni were molecularly detected in 780 dog ticks (749 Rhipicephalus sanguineus , 16 Haemaphysalis campaulata and 15 Haemaphysalis verticalis ), while all sampled dog ticks were negative for rickettsial agents (Zheng et al 2017 ). In Xinjiang Uygur Autonomous Region (XUAR), northwestern China, rickettsial agents were prevalent in ticks infesting both domestic animals and wildlife (Guo et al 2015 , 2016 ).…”
Section: Introductionmentioning
confidence: 99%